2018
DOI: 10.1007/s11249-018-0993-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using Alternative Extreme Pressure (EP) and Anti-Wear (AW) Additives with Oxy-Nitrided Samples

Abstract: Oxy-nitriding is a widely used industrial process aiming to improve the tribological properties and performance of components. Previous studies have shown the effectiveness of the treatment with friction and wear performance, but very few have focussed on optimising this behaviour. The lubrication properties of several EP and AW additives were examined to investigate their effectiveness in improving the tribological properties of the layers formed after treatment. Previous studies showed the presence of an oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Notably, a tribochemical reaction occurs during the sliding process in which the anions in ionic liquids such as PF  6 , BF  4 , and NTf  2 react with water to produce phosphates [85], borides [86], and sulfides [87] on the worn surface, respectively [36,88]. Owing to the excellent extreme pressure and anti-wear properties of phosphates, the tribochemical layer formed by PF  6 exhibits the best lubricating performance [89]. On the other hand, the cations in ionic liquids such as Li + , Na + , and K + possess quite different hydrated radii and hydration energies.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a tribochemical reaction occurs during the sliding process in which the anions in ionic liquids such as PF  6 , BF  4 , and NTf  2 react with water to produce phosphates [85], borides [86], and sulfides [87] on the worn surface, respectively [36,88]. Owing to the excellent extreme pressure and anti-wear properties of phosphates, the tribochemical layer formed by PF  6 exhibits the best lubricating performance [89]. On the other hand, the cations in ionic liquids such as Li + , Na + , and K + possess quite different hydrated radii and hydration energies.…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption of additives physically or chemically to the surfaces of metal results in tribofilm, which consequently averts abrasive wear of the surface and reduces friction 117 . Due to the eco‐toxicity effects of some additives currently used, such as molybdenum dithiocarbamate (MoDTC) and zinc dialkyldithiophosphate (ZDDP), there has been a great interest in the use of eco‐friendly additives that may be of the organic or inorganic source 118 …”
Section: General Overview Of Biolubricantsmentioning
confidence: 99%
“…Experts in tribology employ the science and notion of tribology studies concerning the interacting surface in relative motion to investigate friction, wear, and lubricity of lubricants 163 . Generally, friction is the resistance when two bodies are in motion resulting in wear and tear 118,119 . The studies and impact of tribology have expanded across diverse disciplines, which cannot be covered in this review.…”
Section: Chemical Modification Of Oils For Biolubricants Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Results found that anti-wear protection was reduced from the depleted ZDDP additives during the tribological contact with piston rings and piston skirt region. Khan et al (2018) investigated the tribological performance of oxy-nitrided samples with anti-wear and extreme pressure additive sulphurized olefin (SO), tricresyl phosphate (TCP) additives and ZDDP. SO or TCP additives have no effect on friction because of lack of interaction with the less-reactive iron nitride layer and their roles as anti-wear additives.…”
Section: Introductionmentioning
confidence: 99%